PROCESS OPTIMIZATION FOR Bacillus sp. RP1 ENDOGLUCANASE GENE EXPRESSION BY Escherichia coli BL21 (DE3)/egc - Victor, Hans
Cellulases are one of the most used enzymes in industrial processes. Examples of industries which utilize cellulases are bioconversion industry, detergent industry, paper and pulp industry, food industry, feed industry, fermentation industry, textile industry and others. In an effort to increase production, industries have developed strategies such as isolating new cellulase producing strains, genetic engineering and process optimization since the last 50 years. One endoglucanase producing strain, Bacillus sp. RP1 was isolated from hot springs. The ribosome binding site and coding sequence of the endoglucanase gene (egc) from Bacillus sp. RP 1 was cloned into pGEM-T Easy. The recombinant plasmid was used to transform E. coli BL21 (DE3). Cloning was followed by process optimization through medium design. Medium design was started by selecting medium composition using Plackett-Burman method. The medium components tested were rice hull, molasses, ammonium chloride, urea and fishmeal. Rice hull and molasses were found to be the factors most influencing enzyme activity and dry cell weight, respectively. The next step involved Box-Behnken method and response surface methodology to optimize the responses against molasses concentration, rice hull concentration and fermentation time. The concentration intervals used to test were 1%, 5,5% and 10% while the fermentation time used were 24, 36 and 48 hours. The conditions which optimized both enzyme activity and dry cell weight were 7,45% molases, 6,45% rice hull and 39,52 hours of fermentation.